GROWTH RESPONSE, FLOCK UNIFORMITY, ORGAN WEIGHT, ABDOMINAL FAT, CARCASS YIELD AND HEPATIC HISTOLOGY OF FINISHER BROILER CHICKEN FED TOASTED PIGEON PEA SEED MEAL - Ojediran, Taiwo; Emiola, Adewale (Journal of Agricultural Sciences (Belgrade), 2021)
Three hundred (300) 21d old (Arbor-acre) broiler chicks apportioned to five (5) dietary groups of sixty (60) birds each, further replicated six (6) times were fed toasted pigeon pea seed meal to assess the performance, flock uniformity, organ weights, carcass yield and hepatic histology at the finisher phase. A maize-full fat soybean meal diet served as the control diet (I).  The toasted Pigeon pea seed meal was incorporated to replace full fat soybean meal at 12.5%, 25.0%, 37.5% and 50.0% in diets II, III, IV and V respectively. Toasting improved the protein content, ether extract, fibre content, metabolizable energy and reduced the anti-nutrients except oxalate. The final weight, total weight change, average weight gain and feed conversion quotent were significant influenced (P0.05). The eviscerated weight, breast yield, thigh yield, kidney and abdominal fat were also influenced (P
Keywords: broiler, Cajanus cajan, growth response, organ weight, carcass yield